THE EFFECT OF COVID-19 HISTORY ON CARDIORESPIRATORY FITNESS OF HAJJ PILGRIM CANDIDATES - Ikrar Abdillah Muryasani; Sri Wahyudati; Erna Setiawati (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: Hajj pilgrims are expected to be able to walk a minimum of 12 kilometers. Therefore, good physical fitness is required. COVID-19 is a disease that can cause deconditioning of heart and lung function. Objective: The purpose of this study was to determine the effect of COVID-19 history on cardiorespiratory fitness of hajj pilgrim candidates. Methods: This cross-sectional study was conducted on prospective hajj pilgrim candidates in Salatiga City aged 50-70 years who fit the inclusion criteria. Subject characteristics such as age, comorbid history, and exercise history were collected from subject interviews. Body Mass Index (BMI) was measured by calculating height and weight. Physical activity history was assessed using Indonesian version of the International Physical Activity Questionnaire (IPAQ). Cardiorespiratory fitness was assessed using the six minutes walking test (6MWT). Data were analyzed using comparative test. Results: A total of 32 subjects with a history of COVID-19 with 31 mild symptoms and 1 moderate symptom, and 101 subjects without a history of COVID-19 were included as research subjects. There was significant difference in age (p=0.006) and education (p=0.003) between subject with COVID-19 history and without COVID-19 history (p=0.006). The VO2max result from 6MWT in subjects with history of COVID-19 were significantly lower than those in subjects without a history of COVID-19 (p=0.007, 14.54±3.54 mL/kg/min vs 16.36±3.19 mL/kg/min). Conclusion: COVID-19 history affects the cardiorespiratory fitness of hajj pilgrim candidates. Endurance training should be recommended for Hajj pilgrim candidates with a history of COVID-19 to improve cardiorespiratory fitness.